Influence of Stress, Time of First Sucking, Gravidity, Type of Cesarean Section, Pethidine, and Oxytocin to Onset Time of Lactation in Mothers after Cesarean Delivery - Boondee, Chananrat; Phahuwatanakorn, Wanna; Limruangrong, Piyanun; Chanprapaph, Pharuhas (Journal of The Royal Thai Army Nurses, 2023)
This predictive study aimed to study influence of stress, time of first sucking, gravidity, type of cesarean section, pethidine, and oxytocin to onset time of lactation in mothers after cesarean delivery. The subjects were 101 mothers with cesarean section who attended in the postpartum care unit in University Hospital, Bangkok and Tertiary care unit, Nakornnayok.Personal data record form, Drugs used record form, Onset time of lactation record, and Stress Test Questionnaire (ST-5) were used for data collection. The data were analyzed by using descriptive, Pearson’s product moment correlation coefficient and Multiple linear regression analysis. The findings revealed all independent variables together statistically significantly predicted the onset of lactation by 50.3 (F = 15.833, p < .01) Pethidine (B = .554, p < .01), time of first sucking (B = .600, p < .01) and gravidity (B = -7.465, p < .01) can predicted onset of lactation statistically significantly. The findings revealed all independent variables together statistically significantly predicted the onset of lactation by 50.3 (F = 15.833, p < .01) Pethidine (B = .554, p < .01), time of first sucking (B = .600, p < .01) and gravidity (B = -7.465, p < .01) can predicted onset of lactation statistically significantly. The suggestion from the study are that nurse midwife should initiate breastfeeding immediately after cesarean section especially first time mothers. In addition, drug for pain relief is used as necessary or using nonpharmacological for pain relief method.